Culture as Fourth Pillar of Sustainable Development: Perspectives for Integration, Paradigms of Action - Sabatini, Francesca (European Journal of Sustainable Development, 2019)
The paper explores the relationship between culture and sustainable development. In particular, it advocates the introduction of cultural sustainability as a fourth pillar of sustainable development. A first section explores the existing research on the topic, and focuses on the notion of culture itself and how it should be intended in the context of sustainable development. Then, the existing debate over culture’s position among the three pillars of sustainable development is presented. In the second section, the issue of assessing sustainability in cultural policies is addressed. The proposed approach suggests the interconnection of economic, societal and artistic dimensions of evaluation, thus going beyond the instrumental view of culture which is common in the sustainability discourse. Culture-driven sustainable development is presented in the third section: policies concerning the use of tangible heritage, the development of cultural districts and participatory practices for the performing arts are analysed; their ability to combine artistic merit and positive impacts on the other dimensions of sustainable development is eventually assessed. Conclusively, cultural policies and practices prove able to generate sustainable growth at all levels, not least the creative and artistic one; as a consequence culture can be fully considered a fourth pillar of sustainable development.